THE ASSESSMENT OF SENSITIVITY OF BIOTIC INDICES IN DETERMINING SYMPTOMS AND LEVELS OF DISTURBANCE USING MACROBENTHIC ASSEMBLAGE DATA - Sapto Purnomo Putro (JOURNAL OF COASTAL DEVELOPMENT, 2011)
a large number of techniques, including a variety of indices, have been proposed and developed forassessment. Structural and functional variability have been summarized through both univariate andmultimetric indices as integrative indicators in environmental monitoring programs. In general, multimetricindices are considered to be sensitive, stable, and robust, thus offer a promising approach for ecologicalassessment. This study is aimed to assess the degree of sensitivity for several indices in terms of their abilityto determine environmental changes. Based on macrofaunal data, several univariate and multimetric indiceswere used to assess and compare the level of disturbance at fallowed farm and reference (control) sites. Thetwo multimetric indices, the AZTI’s Marine Biotic Indices (AMBI) and Ecological Quality Ratio (EQR), wereused as integrative indicators to assess the categorisation of each sampled site. The results showed that acombination of multimetric index and univariate indices provide a better assessment. The categoriesdetermined by multimetric indices seem to be in accordance with level of disturbance expressed by thetrophic analysis, multivariate and graphical analyses used in this study. The AMBI has the ability to detectlarge scale differences among sites. However, AMBI was unable to discriminate slight changes in themacrobenthic assemblages between sites, as have been exposed by EQR.